Imaji Kebutuhan Konsumsi Melalui Akun Media Sosial - Chininta Rizka Angelia (Universitas Multimedia Nusantara, 2021)
This study’s motivated by competitive rivalry among producers which encourages them to develop a marketing strategy for the sake of absorption abundance of production. The producer created artificial needs through system of signs on social media. This study aimed to dismantle the use of system of signs on social media that carried producers to raise consumption. According to Consumer Society Theory by Jean Baudrillard, this study used a critical paradigm with The Semiotic Analysis Method of Roland Barthes. The result showed that the producer slipped marketing activities through the system of signs in endorser’s photos on Instagram. Other findings in this study’s there’s a mutual relationship between producer and endorser. Keywords: consumer society, endorsement, social media, Instagram, semiotic, roland barthes